2008
DOI: 10.2166/wh.2009.109
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Cryptosporidium oocyst detection in surface waters of Meru, Kenya as determined by two isolation methods followed by PCR

Abstract: Meru, Kenya has watersheds which are shared by wildlife, humans and domesticated animals.These surface waters can be contaminated by the waterborne pathogen Cryptosporidium. To quantify the seasonality and prevalence of Cryptosporidium in Meru regional surface waters, we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Endemic cryptosporidiosis has also been associated with the onset of the rainy season in Guinea Bissau (26), Uganda (29), Malawi (25), and Brazil (24). A recent study from Kenya also documented increased oocyst contamination of surface waters at the end of the rainy season, which was consistent with the timing of human infections in the region (20). However, cryptosporidiosis has been reported to occur in the spring season in South Korea (6), in the summer and autumn months in Israel (12), and in the cooler months of November to April in Kuwait (28).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Endemic cryptosporidiosis has also been associated with the onset of the rainy season in Guinea Bissau (26), Uganda (29), Malawi (25), and Brazil (24). A recent study from Kenya also documented increased oocyst contamination of surface waters at the end of the rainy season, which was consistent with the timing of human infections in the region (20). However, cryptosporidiosis has been reported to occur in the spring season in South Korea (6), in the summer and autumn months in Israel (12), and in the cooler months of November to April in Kuwait (28).…”
Section: Discussionmentioning
confidence: 68%
“…in their stool samples by microscopy. Children from Delhi showed a higher prevalence (34/970 [3.5%]) (P ϭ 0.055) than children from the 2 southern Indian centers in Vellore (20 25] months) (P ϭ 0.024). Most children were male (67.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Purification by IMS, including identification by immunofluorescence assay (FA) recommended by the US-EPA method 1622 in 2001 has been widely used with recovery rates varying from 40.0 to 100% [5][6][7][8]10]. Apart from IMS, densitybased purification methods, such as sucrose floatation and Percoll-sucrose centrifugation were also applied for purifying oocysts from very turbid water samples [9,11,14]. In the present spiked water sample study, we found that sucrose floatation method enhanced with immunofluoresence assay (SF-FA) showed slightly higher purification efficiency than IMS-FA, especially in high turbidity waters.…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, there has been only one small-scale study in Kenya, in which Cryptosporidium oocysts in nine surface water samples were genotyped (36). Because the stringency of wastewater treatment and discharge and the intensity of animal husbandry are very different between developing countries and industrialized nations, observations made in the latter cannot be applied easily to the former.…”
mentioning
confidence: 99%